Prevalence of toxoplasmosis among miscarried women and the effect on embryo in Thi -Qar province southern – Iraq - Ahmed salman abdulhasan (University of Thi-Qar Journal of Science, 2022)
Toxoplasma gondii is a widespread worldwide and is one of the causes of miscarriage in women who are pregnant .Toxoplasma gondii infection among miscarried  women in Thi-Qar province was  investigated  in this study.  A total of 120 blood samples of aborted women and 80 samples of blood were taken  from women who had not undergone miscarriage while pregnant (comparison group) and for the period from November 2018 to January 2019 and with ages ranging from 15 to 44 years. Anti-Toxoplasma IgM and IgG antibodies were detected using an enzyme-linked immunosorbant assay (ELISA).The results showed that the total incidence of T. gondii among women with miscarriage was 59/120 (49.1%) compared with the standard group (women without miscarriage) 5/80 (6.2%). The rate of infection was IgG 41.6%, IgM 5% and IgG & IgM togather 2.5% among miscarried  women. The age group with the highest percentage was the range of  (25-34) year ,was(45.7%) and the lowest percentage was 22 % in the range of ( 35-44 )year  age range. The highest rate of infection was in the first period of pregnancy 52.5% and the lowest was in the third period of pregnancy 18.6%   women who had a single miscarriage have the highest prevalence of infection (44%) and the lowest was in women who have multiple miscarriage (23.7%).